The integrative analysis of transcriptome and metabolome reveals differences in raw foie gras performance induced by different force-feeding intensities in male Tianfu meat geese - Teng, Yongqiang; Wei, Rongxue; Peng, Shanjing; Li, Jiang; Ning, Rong; Luo, Zhaoyun; Wei, Shouhai; Bai, Lili; Zhou, Li; Han, Chunchun (Frontiers in Veterinary Science, 2025)
We aimed to explore the influence of different force-feeding intensities on foie gras performance. Geese were force-fed with A (force-feeding four times per day and lasting 28 days) and B (force-feeding 5 times per day and lasting 18 days) at two levels of force-feeding intensities in this study. An integrative analysis of the liver transcriptome, amino acid metabolome, and long-chain fatty acid metabolome was performed. In serum, the levels of blood glucose, insulin, triglyceride (TG), and very low-density lipoprotein (VLDL) of the B group were significantly higher than those of the A group (p < 0.05). The B force-feeding intensity induced more severe steatosis in the goose liver. Transcriptome analysis showed that 948 upregulated differentially expressed genes (DEGs) and 519 downregulated DEGs were identified (A vs. B); key DEGs G6PD, IGF1, IGF2, and MLX were upregulated; LPL, IRS1, IRS4, and IGF1R were downregulated. Principal component analysis (PCA) indicated that there was clear separation and discrimination in liver free amino acids profiles and long-chain fatty acids profiles between the A and B groups, respectively. The Lys level of the B group was significantly higher than that of the A group (p < 0.05). The highest enrichment pathway of different amino acids was valine, leucine, and isoleucine biosynthesis, whereas alanine, aspartate, and glutamate metabolism was the pathway involved with the highest impact score. The levels of saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), unsaturated fatty acids (UFAs), C14:0, C16:1, C16:0, C18:2n6c, C18:1n9c, and C18:0 of the B group were significantly higher than those of the A group (p < 0.05). The highest impact score pathway related to different fatty acids was linoleic acid metabolism, and the highest enrichment pathway involved in different fatty acids was biosynthesis of unsaturated fatty acids. In conclusion, liver DEGs involved in glucolipid metabolism, different free amino acids, and different fatty acids collectively shaped the foie gras performance difference induced by different force-feeding intensities.